Factors Influencing Academic Achievement of Students in The Engineering Course at Sultan Abdul Halim Mu'adzam Shah Polytechnic - Izyan Wahida Binti Zainuddin, (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This study aims to examine the factors influencing the academic achievement of students in the Diploma in Building Services Engineering course at Sultan Abdul Halim Mu'adzam Shah Polytechnic. The identified factors include attitudes, interests, and teaching methods of lecturers in the classroom. The study involved 40 respondents comprising fifth-semester students. The research instrument used was a questionnaire, and the data were analyzed using IBM Statistical Package for Social Science (SPSS) 20 to obtain frequency values, percentage means, and standard deviations. The Cronbach's alpha value obtained was 0.88. The study found that the highest mean score for the factors influencing student achievement was lecturer teaching (mean score = 4.37) in the classroom. This was followed by student attitudes (mean score 4.34), and the last factor was student interest with a score of 4.27. In conclusion, all the factors studied showed a significant relationship in influencing the academic achievement of students in the engineering course. However, improvement measures should be implemented to ensure the continued excellence in students' academic performance.